Perkembangan Pasar Modal Dalam Perekonomian di Negara Indonesia - Alfa Dwi Apriliani; Mila Amelia; Siti Maryani; Dedi Mulyadi (Jurnal Ilmiah Wahana Pendidikan, 2023)
The economy of the capital market country must be able to facilitate the development of the market economy and the private sector will be the vehicle for economic activity. In relation to the problem of economic development, improving the capital structure of the business world is a must in order to increase efficiency and strengthen the competitiveness of companies in order to face increasingly sharp competition in the era of globalization. The purpose of this study is to determine the development of the capital market in Indonesia using a literature study method. Sources of this literature study were obtained from various books, journals, and other references that can be used and related to the development of capital markets in the economy in Indonesia. Based on the research results, the role of the capital market as a source of corporate funding that has implications for the country's economy is not only an alternative but has been able to become the main source of funding.